Chromophobe renal cell carcinoma with neuroendocrine and neuroendocrine-like features. Morphologic, immunohistochemical, ultrastructural, and array comparative genomic hybridization analysis of 18 cases and review of the literature - Michalová, Květoslava; Martínek, Petr; Ohe, Chisato; Kuroda, Naoto; Bulimbasic, Stela; Condom Mundo, Enric; Perez Montiel, Delia; Lopez, Jose I; Daum, Ondřej; Rotterová, Pavla; Vaňková, Bohuslava; Daumová, Magdaléna; et al. (Annals of diagnostic pathology, 2015)
Chromophobe renal cell carcinoma (CRCC) with neuroendocrine differentiation (CRCCND) has only recently been described. Eighteen cases of CRCC with morphologic features suggestive of neuroendocrine differentiation were selected from among 624 CRCCs in our registry. The tissues were fixed in neutral formalin, embedded in paraffin, cut into 4- to 5-μm-thick sections, and stained with hematoxylin and eosin. As CRCC with neuroendocrine features, tumors with following morphology were suggested: (1) trabecular/palisading/ribbon-like, gyriform, insular, glandular, and solid pattern; (2) uniform polygonal cells formed in small islets; and (3) cribriform pattern in combination with palisading. Selected cases were further analyzed using immunohistochemistry, electron microscopy, array comparative genomic hybridization, and fluorescence in situ hybridization. Cases were classified as CRCCND or CRCC with neuroendocrine-like features (CRCCND-L) based on the immunohistochemical expression of neuroendocrine markers: CRCCND, 4 cases, age range 49 to 79 years, size ranged from 2.2 to 22 cm, and CRCCND-L, 14 cases, age range 34 to 74 years, size range 3.8 to 16.5 cm. Follow-up information was available for 11 of 18 patients aged 0.5 to 12 years. Two of 4 CRCCNDs showed aggressive clinical course with metastatic spreading. Chromophobe renal cell carcinomas with neuroendocrine differentiation were focally positive for CD56 (4/4), synaptophysin (4/4), chromogranin A (1/4), and neuron-specific enolase (3/4). All 14 CRCCND-Ls were mostly negative or very weakly focally positive for some of the aforementioned markers. All 18 tumors were positive for cytokeratin 7 and CD117. Ultrastructural analysis showed poorly preserved neuroendocrine granules only in 2 of 4 analyzed CRCCNDs. Losses of chromosomes 1, 2, 6, and 10 were found in all analyzable CRCCNDs, whereas multiple losses (chromosomes 1, 2, 6, 10, 13, 17, and 21) and gains (chromosomes 4, 11, 12, 14, 15, 16, 19, and 20) were found in CRCCND-L.
Keywords: dospělí; metastázy nádorů; diferenciální diagnóza; srovnávací genomová hybridizace; Female; Adult; ženské pohlaví; Immunohistochemistry; lidé; karcinom z renálních buněk; imunohistochemie; Diagnosis, Differential; Kidney Neoplasms; Carcinoma, Renal Cell; Male; Aged; Comparative Genomic Hybridization; Neuroendocrine Tumors; nádory ledvin; lidé středního věku; senioři; mužské pohlaví; Neoplasm Metastasis; Middle Aged; neuroendokrinní nádory; Humans